The Adductor Strengthening Programme prevents groin problems among male football players: A cluster-randomised controlled trial - Haroy, J.; Clarsen, B.; Wiger, E. G.; Oyen, M. G.; Serner, A.; Thorborg, K.; Hölmich, P.; Andersen, T. E.; Bahr, R. (British Journal of Sports Medicine, 2019)
Background: Groin injuries represent a considerable problem in male football. Previous groin-specific prevention programmes have not shown a significant reduction in groin injury rates. An exercise programme using the Copenhagen Adduction exercise increases hip adduction strength, a key risk factor for groin injuries. However, its preventive effect is yet to be tested. Aim: To evaluate the effect of a single-exercise approach, based on the Copenhagen Adduction exercise, on the prevalence of groin problems in male football players. Methods: 35 semiprofessional Norwegian football teams were cluster-randomised into an intervention group (18 teams, 339 players) and a control group (17 teams, 313 players). The intervention group performed an Adductor Strengthening Programme using one exercise, with three progression levels, three times per week during the preseason (6-8 weeks), and once per week during the competitive season (28 weeks). The control group were instructed to train as normal. The prevalence of groin problems was measured weekly in both groups during the competitive season using the Oslo Sports Trauma Research Center Overuse Injury Questionnaire. Results: The average prevalence of groin problems during the season was 13.5% (95% CI 12.3% to 14.7%) in the intervention group and 21.3% (95% CI 20.0% to 22.6%) in the control group. The risk of reporting groin problems was 41% lower in the intervention group (OR 0.59, 95% CI 0.40 to 0.86, p=0.008). Conclusion: The simple Adductor Strengthening Programme substantially reduced the self-reported prevalence and risk of groin problems in male football players.